Contested perceptions interactions and relations between China, Korea, and Japan since the seventeenth century - Okamoto, Takashi 1965-
"The histories of China, Korea, and Japan have been intimately intertwined for centuries. But of these three countries, it was Korea that occupied the pivotal geopolitical position. The Korean Peninsula shaped the dynamics of international interactions and relations in East Asia which, up until the start of the twentieth century, were underpinned by systems of order wholly removed from the sovereign state system we recognize as ubiquitous today. Contested Perceptions examines the coexistence of 'neighborly relations' between Japan and Korea and 'tributary relations' between Korea and the Qing dynasty from the seventeenth to the nineteenth century, and Korean 'tributary autonomy' in the late nineteenth century. It provides a cogent analysis of the differing perceptions that determined the success or failure of these past systems of order and their influence upon the balance of power in East Asia from the seventeenth century to modern times. Delving into the history of East Asian international relations, diplomacy, and power politics, this book elucidates the events that led to the Sino-Japanese and Russo-Japanese wars, and the conflicts of interest that have defined these nations to the present day."--Page 4 of cover.